United States : 2018 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2018)
Unemployment is low, inflation is well contained, and growth is set to accelerate. During the course of this administration, the economy is expected to enter the longest expansion in recorded U.S. history.